2022
DOI: 10.7554/elife.72482
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural segregation of overlapping helices in HIV-1

Abstract: Overlapping coding regions balance selective forces between multiple genes. One possible division of nucleotide sequence is that the predominant selective force on a particular nucleotide can be attributed to just one gene. While this arrangement has been observed in regions in which one gene is structured and the other is disordered, we sought to explore how overlapping genes balance constraints when both protein products are structured over the same sequence. We use a combination of sequence analysis, functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Evolutionary constraint in OLGs has not yet been studied in much detail for specific gene pairs, apart from the case of overlapping genes in HIV-1. In this virus it has been shown first that constrained regions of overlapping genes in a pair are organized so as not to overlap (79) and second that even when domains do overlap, functionally constrained residues in one protein are encoded overlapping more mutable codons in the other protein (80). Further, constraint can be conceived either negatively or positively.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary constraint in OLGs has not yet been studied in much detail for specific gene pairs, apart from the case of overlapping genes in HIV-1. In this virus it has been shown first that constrained regions of overlapping genes in a pair are organized so as not to overlap (79) and second that even when domains do overlap, functionally constrained residues in one protein are encoded overlapping more mutable codons in the other protein (80). Further, constraint can be conceived either negatively or positively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Frankel et al has demonstrated that functional regions of rev are segregated from functional regions of the overlying tat and env genes, permitting mutations that affect the activity of one protein at a time (35,36). RRE activity is similarly robust to nonsynonymous changes in Env, as the functional consequence of these mutations can be compensated by additional synonymous changes in other portions of the RRE (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The A8079G mutation is situated in the overlapping region of rev and env genes, designed to be a silent mutation for Rev but inducing the substitution of glutamine with glycine at position 771 in Env. We selected this mutation because this amino acid substitution was shown to only moderately reduce HIV-1 fitness in vitro 89 . A8975C and A8989T are located in the 3′ UTR (U3) of the HIV-1 RNAs.…”
Section: Methodsmentioning
confidence: 99%